Legorreta+legorreta - Cuito, Aurora ([S.l.] : Te Neues Publishing Company, 2002)
In spite of its monumentality, the architecture of Legorreta + Legorreta is conceived for us to live in: it suits our needs, our appetites, and our emotions. Some of the best examples are seen in the vestibules of the Center of Visual Arts and of the Sheraton Hotel in Bilbao. Geometric pure and timeless forms instill rotundity and clarity into the complicated projects. Even in large complexes, like the Chiron Laboratories, or the Egade Graduate School, privacy and simplicity is preserved. The treatment of light also aids them in creating different spaces without any need of walls or separators. The application of color is a most important priority, especially in projects set in their native Mexico. There are tones that the architects use to dramatize spaces which intensify the personal experience of the people in the buildings. All of these ingredients integrate architecture, landscaping, and interior decoration into a single discipline that respects the place and the traditions.